(untitled) (Modern education and development, 2025)
Central Asia is known for its great heritage and the big contribution for the world history. Its nature is also known for picturesque views namely forests, mountain resources, and river sides, However, in the beginning of 19th century, political issues had a sweeping effect on its ecology. Drying of the main water source, the Aral Sea (68,000 square kilometers before, 26,300 square kilometers now), created a number of environmental and economical based barriers for Central Asian countries. This article will explore the causes and effects of this habitual catastrophe led by human mismanagement and natural disaster as well as the providing with the measures that are taken.